Poziom chlorofilu a i b w liściach krzewów podszytowych w grabowo-dębowych lasach lasostepu Ukrainy Zachodniej - Zaïka, Volodymyr; Bondarenko, Taras (Leśne Prace Badawcze, 2018)
In this study, the biosynthesis of the plastid pigments chlorophyll a and b was examined for the most common shrubs in hornbeam-oak forest stands of the Western forest-steppe zone of Ukraine. The characteristics of the pigments’ biosynthesis were determined in terms of plant species, vegetation period and growth conditions (under canopy cover and out in the open). The gathered data on the changes of the pigment complex with respect to the examined variables confirms the sensitivity of plastid pigment biosynthesis to environmental factors.